UPAYA RESTRUKTURISASI KAWASAN HUTAN GUNUNG LIO KABUPATEN BREBES PASCA BENCANA TANAH LONGSOR BERBASIS KEARIFAN LOKAL MELALUI COMMUNITY DEVELOPMENT - Trimasukmana, Danang Junior (Indonesian Journal of Conservation, 2018)
The role of social institutions is very important as local wisdom because it can facilitate the community when planning, coordinating, and controlling activities to rehabilitate the environment. Local customary institutions also play a role in the development of rural areas, especially highland communities that function to build social capital: social, cultural, economic and environmental values, which are a wealth of local wisdom. By using social capital based on local wisdom, the community can rehabilitate forests with an effective local leadership system